Persepsi Mahasiswa terhadap Layanan Bimbingan dan Konseling Berbasis Nilai Agama dalam Proses Pembentukan Karakter - Shafa Fajriandini Cahyadi; Mona Maimun Mustofa; Sandhian Lasti Aimma; Budi Johan; Khaila Alfiory Lestari Legowo Putri (Program Studi Bimbingan dan Konseling, Universitas Negeri Jakarta, 2025)
This study aims to determine student perceptions of religious value-based guidance and counseling services in the character building process. This approach uses a qualitative case study method. The results showed that students have a positive perception of counseling services that integrate religious values, because they are considered capable of providing moral and spiritual direction that has an impact on character building, such as responsibility, honesty, empathy, and discipline. This service is also considered to help students in dealing with inner conflict and academic pressure with a more humanist and religious approach. This shows the importance of strengthening religious values in counseling practices to support students' personal development.